Association of mass media exposure with combustible and smokeless tobacco use among Indian population: findings from a panel survey - Ronak Paul; Rashmi Rashmi; Shobhit Srivastava (BMC, 2022)
Abstract Background Despite introducing different policies and initiatives, India is recognized as one of the global players in the tobacco epidemic race. Our study explores the association between tobacco consumption and mass media exposure among the Indian population, considering the contextual factors affecting the clustering at the community and state levels. Methods Using two waves of the India Human Development Survey (IHDS) conducted in 2005 and 2012 for 16,661 individuals, the present study explores the association of mass media exposure and tobacco consumption in the short-term and the long-term period of Cigarettes and Other Tobacco Products Act (COTPA) implementation, which came into existence in 2004. Bivariate analysis using the chi-square test for association showed the correlation of tobacco consumption with its respective predictors. Multivariable analysis using three-level random intercept logit models showed the adjusted association between tobacco consumption and its relevant covariates and the extent of clustering of tobacco consumption behaviour of persons in the communities and states. Results We found that watching television (TV) [(OR:1.03; CI:0.92-1.15) in 2004-05 and (OR:0.99; CI:0.88-1.12) in 2011-12], listening radio [(OR: 0.99; CI:0.90-1.10) in 2004-05 and (OR:1.04; CI:0.94-1.15) in 2011-12] and reading newspaper [(OR:1.02; CI:0.91-1.15) in 2004-05 and (OR:0.96; CI:0.87-1.06) in 2011-12] did not have any significant effect on consumption of combustible tobacco. Similarly, no effect of mass media was found on smokeless tobacco consumption. Further, the clustering of combustible and smokeless tobacco usage was higher at the community level than at the state level. In both rounds, smokeless tobacco consumption was found to be higher than combustible tobacco. Discussion The present study provides evidence that COTPA has achieved its aim of nullifying the significant effect of mass media on combustible and smokeless tobacco consumption among the Indian population. However, the influence of state- and community- level clustering had failed in curbing the increment of smokeless tobacco consumption. There is a need for policy reforms to curb the significant impact of factors that promotes smokeless tobacco consumption in India. Further, initiatives must focus on specific communities from high-risk states, reducing the time and cost required for implementation.